Shariah information disclosure and its effect on financial perfomance among SMEs in Malaysia - Noor Azman, Ain; Ali, Noor Azman; Mahat, Fauziah; Mat Daud, Zaidi (Society for Science and Education, 2020)
Introduction: Shariah disclosure has become an important aspect in a Small-Medium Enterprises (SMEs). The disclosure of shariah information would enhance the transparency and accountability of SMEs towards its stakeholders which in return helps promote the long-term profitability and sustainability.